Early Pregnancy Justification of Low Economic Status “Poverty”: Adolescent Sexual and Reproductive Health - Health Facility Based Study - Francis, WABWIRE Paul; Evarine, NAMPEWO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Early pregnancy in the context of this research is defined as “pregnancy of humans less than20 yrs as noted to be an old national / worldwide tradition.” The study purposed to establish themagnitude and the in-depth relationship between early pregnancy and low economic status. It was adescriptive, cross-sectional study that adopted quantitative data collection and analysis approach inpurposively selected population of “444” mothers attending maternal child health services. Data wascollected using semi-structured questionnaire. Findings were highly associated with Individual,Family, Communal and Spouse factors under varying levels. Data involving 100 homes predicted H–1 being wealthier than H-2.